MECHANICAL PROPERTIES OF CONCRETE BRICKS WITH THE ADDITION OF SUGARCANE BAGASSE ASH - Masthura Masthura; Indah Sawitri; Abdul Halim Daulay (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2019)
A research has been done on the mechanical bricking test with the addition of bagasse ash. In this study, the tested bricks tested were compressive and flexural strength. The purpose of this study was to determine the effect of adding bagasse ash to the mechanical properties of the concrete brick. The percentage variation of bagasse ash, cement, and sand are 0%:30%:70%, 5%:25%:70%, 10%:20%:70%, 15%:15%:70%, 20%:10%:70% with Water Cement Ratio of 0.5 in all variations. The addition of bagasse ash as a substitute for cement significantly affected the characteristics of the concrete brick. With the addition of bagasse ash in a mixture of 5-20% causes the compressive strength to decrease. While the flexural strength has increased in the variation of the mixture of 5-10% and has decreased in the variation of the mixture of 15-20%. The most optimal composition of mixing bagasse ash, cement, and sand is at 5% mixture variation for compressive strength and flexural strength testing because it meets SNI 03-0348-1989 standards. Whereas the other mixed variations are not optimal. Keywords : Bagasse ash, Compressive Strength, and Flexural Strength.